2016
DOI: 10.1007/s00253-016-7402-2
|View full text |Cite
|
Sign up to set email alerts
|

Multiple paths of electron flow to current in microbial electrolysis cells fed with low and high concentrations of propionate

Abstract: Microbial electrolysis cells (MECs) provide a viable approach for bioenergy generation from fermentable substrates such as propionate. However, the paths of electron flow during propionate oxidation in the anode of MECs are unknown. Here, the paths of electron flow involved in propionate oxidation in the anode of two-chambered MECs were examined at low (4.5 mM) and high (36 mM) propionate concentrations. Electron mass balances and microbial community analysis revealed that multiple paths of electron flow (via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 74 publications
3
32
0
Order By: Relevance
“…In the O.C reactors, complete removal of propionate was facilitated through microbial partnerships between fermenters ( Smithella and Syntrophobacter ) and hydrogenotrophic and acetoclastic methanogens. In our earlier study30, we demonstrated that propionate degradation in MECs occurred via a microbial partnership between fermenters and Geobacter , and low propionate removal (80% removal) was observed at 36 mM (similar to the concentration used in the current study) compared to complete removal at 4.5 mM30. Methanogenesis was not an important electron sink in our earlier study at both propionate concenrations tested, whereas methanogenesis (via hydrogenotrophic methanogens) was an important sink in the current sudy.…”
Section: Discussionsupporting
confidence: 43%
See 4 more Smart Citations
“…In the O.C reactors, complete removal of propionate was facilitated through microbial partnerships between fermenters ( Smithella and Syntrophobacter ) and hydrogenotrophic and acetoclastic methanogens. In our earlier study30, we demonstrated that propionate degradation in MECs occurred via a microbial partnership between fermenters and Geobacter , and low propionate removal (80% removal) was observed at 36 mM (similar to the concentration used in the current study) compared to complete removal at 4.5 mM30. Methanogenesis was not an important electron sink in our earlier study at both propionate concenrations tested, whereas methanogenesis (via hydrogenotrophic methanogens) was an important sink in the current sudy.…”
Section: Discussionsupporting
confidence: 43%
“…Based on the aforementioned studies, it seems that the complete degradation of propionate at elevated concentrations in MECs requires microbial partnerships between fermenters, hydrogenotrophic methanogens and Geobacter . Whereas, at low propionate concentration microbial partnership between Geobacter and fermenters was sufficient to achieve complete removal of propionate in MEC30.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations